2014
DOI: 10.1002/bdra.23255
|View full text |Cite
|
Sign up to set email alerts
|

Planar cell polarity gene mutations contribute to the etiology of human neural tube defects in our population

Abstract: Neural Tube Defects (NTDs) are congenital malformations that involve failure of the neural tube closure during the early phases of development at any level of the rostro-caudal axis. The planar cell polarity (PCP) pathway is a highly conserved, noncanonical Wnt-Frizzled-Dishevelled signaling cascade, that was first identified in the fruit fly Drosophila. We are here reviewing the role of the PCP pathway genes in the etiology of human NTDs, updating the list of the rare and deleterious mutations identified so f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 74 publications
0
36
0
Order By: Relevance
“…The first identified mutations were in Vang-like protein 1 (VANGL1) 116 , but since then, mutations in essentially all the core PCP genes have now been identified in human NTD patients. These individual findings are too numerous to list here but have been comprehensively delineated elsewhere 122,123 . Several studies also provide mechanistic insights, revealing that NTD-associated mutations disrupt known interactions among PCP proteins and/or disrupt their subcellular localization 116,124126 .…”
Section: Introductionmentioning
confidence: 95%
“…The first identified mutations were in Vang-like protein 1 (VANGL1) 116 , but since then, mutations in essentially all the core PCP genes have now been identified in human NTD patients. These individual findings are too numerous to list here but have been comprehensively delineated elsewhere 122,123 . Several studies also provide mechanistic insights, revealing that NTD-associated mutations disrupt known interactions among PCP proteins and/or disrupt their subcellular localization 116,124126 .…”
Section: Introductionmentioning
confidence: 95%
“…Mice with genetic disruptions in critical modulators of Wnt/PCP signaling, including Dact1 (Dapper, Frodo), Scribble (Scrib), cadherin EGF LAG seven-pass G-type receptor 1 (Celsr1), Dvl2, Vangl1, and Vangl2, have highly penetrant NTD phenotypes [40,41,42,43,44]. Importantly, human genomic studies of patients with NTDs have also revealed mutations in several of these same Wnt/PCP pathway genes [45,46,47,48,49,50,51,52]. A role for the Wnt/β-catenin pathway is indicated in this process as well.…”
Section: Neural Plate Specification and Neural Tube Formationmentioning
confidence: 99%
“…Here, recessive mutations in vangl2 result in severe neural tube defects associated with abnormal morphogenesis of the floor plate neuroectoderm [6, 7]. Humans with mutations in VANGL1 or VANGL2 also develop neural tube closure defects [8]. Accumulating data also suggest a role for VANGL proteins during tumor progression and invasion [9, 10].…”
Section: Introductionmentioning
confidence: 99%